VD_FINDINFO Jug / 2011 / 150 vom 19. Juli 2011 - VD Tribunal cantonal (2011)
LÉSION CORPORELLE SIMPLE, CONTRAINTEDROIT PÉNAL, PRÉSOMPTION D'INNOCENCE, INJURE, MENACEDROIT PÉNAL, TORT MORAL | 49 al. 1 CO, 123 ch. 1 CP, 123 ch. 2 al. 4 CP, 173 ch. 1 CP, 177 al. 1 CP, 180 CP, 181 CP, 95 ch. 1 al. 3 LCR